A Study on the Relationship Between Self-Efficacy, Psychological Resilience, and Job Burnout of Grassroots Civil Servants: The Moderating Role of the Big Five Personality Traits. Issue 10 (21st October 2022) - Feng, Yuchao; Li, Fangwei; Sun, Hongwei
Abstract : Self-efficacy affects job burnout through psychological resilience. Higher levels of self-efficacy and mental resilience may reduce the job burnout. The mediating effect of resilience can be influenced by neuroticism. Higher levels of neuroticism have a negative effect on the moderating role of self-efficacy on job burnout through psychological resilience. Abstract : Objective: The aim of this study was to investigate the status of self-efficacy, resilience, personality traits, and job burnout of grassroots civil servants, and their relationship. Methods: Grassroots civil servants were randomly selected, and questionnaire survey method was adopted. Results: Civil servants with characteristics such as age, marital status, education level, and length of service were more prone to job burnout. Self-efficacy, resilience, and personality traits were important factors influencing job burnout of grassroots civil servants. Neuroticism played a regulating role in the relationship between self-efficacy and mental resilience. The increase of neuroticism score led to increasing mediation of self-efficacy on job burnout through decreased mental resilience. Conclusions: Higher levels of self-efficacy and mental resilience may reduce job burnout. Higher levels of neuroticism have a negative effect on the moderating role of self-efficacy on job burnout through psychological resilience.